Mechanochemical Functionalization of Oxidized Carbon Black with PLA - Aida Kiani; Mattia Naddeo; Federica Santulli; Valentina Volpe; Mina Mazzeo; Maria Rosaria Acocella (Molecules)
The functionalization of carbon black (CB) represents a promising strategy to enhance its compatibility with polymers while addressing sustainability concerns. In this study, a solvent-free mechanochemical approach (ball milling) is proposed for the functionalization of oxidized carbon black (oCB) with post-consumed polylactic acid (PLA), overcoming the environmental drawbacks of conventional methods that mostly rely on toxic solvents and catalysts. The functionalized carbon black (f-CB) was characterized by Fourier transform infrared spectroscopy (FTIR), elemental analysis (EA), and thermogravimetric analysis (TGA) to confirm the successful modification. At the same time, the influence of f-CB as a nanofiller of residual PLA waste was evaluated using differential scanning calorimetry (DSC) and gel permeation chromatography (GPC), demonstrating its stabilization effect during melt extrusion by preserving the molecular weight of the starting polymer. On the other hand, the dynamic mechanical analysis (DMA) revealed that the addition of f-CB did not negatively affect the mechanical properties of the resulting composite. In conclusion, mechanochemistry was used as a sustainable and unique strategy for the upcycling of waste PLA into a PLA-based composite stabilized by CB functionalized with the waste PLA itself.